Seasons of Love: Chinese millennials' affective amateur musical theatre performances. (2nd January 2020) - MacDonald, Laura
Abstract : Having survived the gruelling gāokǎo (the national entrance exam for university education in China), some Chinese undergraduates view university as a welcome break. Feeling they have sufficiently pleased their parents, they explore the plethora of student societies on campus. The majority of C9 institutions (China's Ivy League) have musical theatre clubs, and draw members ranging from journalism to medicine students. China's 400 million millennials are like no other generation of Chinese, making their enthusiasm for Western musicals, with their uplifting messages of dream fulfilment, potentially significant. Beyond any spectatorship as fans, their amateur performances of musicals provide them with an affective experience, and one that originates outside of China. Singing Jonathan Larson's Rent lyrics about the struggles of East Village bohemians in the 1990s, experiencing Roxie's and Velma's ambition in Chicago, and building a multicultural community in Come From Away offer Chinese millennials a radically different adolescence than their parents'. Having grown up with digital technology, and gaining fluency in English, the younger Chinese now use lyrics from Western musicals as a shorthand to communicate with each other on social media platforms.